Mechanisms of selenium removal by partially oxidized magnetite nanoparticles for wastewater remediation. (September 2021) - Börsig, Nicolas; Scheinost, Andreas C.; Schild, Dieter; Neumann, Thomas
Abstract: Magnetite nanoparticles are a promising cost-effective material for the remediation of polluted wastewaters. Due to their magnetic properties and their high adsorption and reduction potential, they are particularly suitable for the decontamination of oxyanion-forming contaminants, including the highly mobile selenium oxyanions selenite and selenate. However, little is known how the remediation efficiency of magnetite nanoparticles in field applications is affected by partial oxidation and the formation of magnetite/maghemite phases. Here we characterize the retention mechanisms and capacity of partially oxidized nanoparticulate magnetite for selenite and selenate in an oxic system at different pH conditions and ionic strengths. Data from adsorption experiments showed that retention of selenate is extremely limited except for acidic conditions and strongly influenced by competing chloride anions, indicating outer-sphere adsorption. By contrast, although selenite adsorption capacity of oxidized magnetite is also adversely affected by increasing pH, considerable selenite quantities are retained even at alkaline conditions. Using spectroscopic analyses (XPS, XAFS), both mononuclear edge-sharing ( 2 E) and binuclear corner-sharing ( 2 C) inner-sphere selenite surface complexes were detected, while reduction to Se(0) or Se(–II) species could be excluded. Under favourable adsorption conditions, up to pH 8, the affinity of selenite to form 2 C surface complexes is higher, whereas at alkaline pH values and less favourable adsorption conditions 2 E complexes become more dominant. Our results demonstrate that magnetite can be used as a suitable reactant for the immobilization of selenite in remediation applications, even under (sub)oxic conditions and without the involvement of reduction processes. Graphical abstract: Image 1 Highlights: Oxidized magnetite can effectively remediate selenite contaminated wastewaters. No reduction processes are required to remove large amounts of Se oxyanions. Selenite immobilization is driven by formation of inner-sphere adsorption complexes. Partially oxidized magnetite nanoparticles behave like maghemite phases.